Pengembangan Game Edukasi Teraven of Majapahit untuk Mendukung Kemampuan Literasi Numerasi Siswa SMA - Ermawan, Redita Putri; Anjariyah, Deka; Feriyanto, Feriyanto (Lembaga Yasin AlSys, 2025)
Mathematics instruction at SMA Negeri 1 Mojosari, particularly in Grade X trigonometry, remains dominated by conventional media such as PowerPoint and videos, resulting in low student engagement and suboptimal numeracy literacy outcomes. Observations and interviews revealed that approximately 75% of students had not reached the Minimum Mastery Criteria (KKTP) score of 75 in trigonometry quizzes. This study aims to develop the educational game TERAVEN of Majapahit using Construct 2 as a learning medium to enhance high school students’ numeracy literacy, while also assessing its feasibility and student response. The research method employed was Research and Development (R&D) using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Instruments included validation questionnaires by media and content experts, student response questionnaires, and numeracy literacy tests. Validation results showed scores of 89.9% from the media expert and 94% from the content expert, both categorized as